2014
DOI: 10.1007/s00280-014-2466-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and exposure–effect relationships of capecitabine in elderly patients with breast or colorectal cancer

Abstract: This study puts forward new arguments for the treatment of elderly cancer patients who could benefit from capecitabine chemotherapy with acceptable toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…However, no influence of age on the PK of 5-FU or other metabolites has been shown [ 96 ]. Although the impact of FBAL plasma concentrations on clinical toxicity remains unclear, clinically-relevant effects are not expected [ 97 , 98 , 99 , 100 , 101 ]. In one moderate-sized PK study, a lower capecitabine clearance in elderly patients was found ( n = 29), which the authors attributed to the overall number of women included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no influence of age on the PK of 5-FU or other metabolites has been shown [ 96 ]. Although the impact of FBAL plasma concentrations on clinical toxicity remains unclear, clinically-relevant effects are not expected [ 97 , 98 , 99 , 100 , 101 ]. In one moderate-sized PK study, a lower capecitabine clearance in elderly patients was found ( n = 29), which the authors attributed to the overall number of women included.…”
Section: Resultsmentioning
confidence: 99%
“…This was supported by a population PK analysis study including 20 elderly patients, compared to PK data of 40 younger patients from two previous clinical trials, showing no effect of age on the clearance of capecitabine and its metabolites. Although a difference in absorption by age was documented, the authors reported this as not having clinical relevance [ 101 ]. According to the drug’s SmPC, capecitabine should be used cautiously in elderly patients.…”
Section: Resultsmentioning
confidence: 99%
“…The analytes were quantitatively measured by this fully validated UHPLC-MS/MS method in the plasma. As a result, apparent differences of drug concentrations in plasma were found in Cap and its metabolites in absorption and metabolism processes, and several studies also reported these differences [1620]. The drug exposure in vivo has a close relationship with the treatment efficacy and/or side effects, and it was still the promising biomarker for the clinical prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the XLA patient had a slower ability to absorb Cap and increased thymidine phosphorylase (TYMP) activity. Since both low 5′-DFUR levels and induced TYMP activity are negatively associated with Cap-related toxicity [21, 22] and this patient did not show any sign of DRT, the original chemotherapy plan was not adjusted.
Fig.
…”
Section: Case Presentationmentioning
confidence: 99%